The hepatocyte growth factor/mesenchymal epithelial transition factor axis in high-risk pediatric solid tumors and the anti-tumor activity of targeted therapeutic agents - Grundy, Megan; Narendran, Aru (Frontiers in Pediatrics, 2022)
Clinical trials completed in the last two decades have contributed significantly to the improved overall survival of children with cancer. In spite of these advancements, disease relapse still remains a significant cause of death in this patient population. Often, increasing the intensity of current protocols is not feasible because of cumulative toxicity and development of drug resistance. Therefore, the identification and clinical validation of novel targets in high-risk and refractory childhood malignancies are essential to develop effective new generation treatment protocols. A number of recent studies have shown that the hepatocyte growth factor (HGF) and its receptor c-MET influence the growth, survival, angiogenesis, and metastasis of cancer cells. Therefore, the c-MET receptor tyrosine kinase and HGF have been identified as potential targets for cancer therapeutics and recent years have seen a race to synthesize molecules to block their expression and function. In this review we aim to summarize the literature that explores the potential and biological rationale for c-MET-pathway targeting in common and high-risk pediatric solid tumors. We also discuss selected recent and ongoing clinical trials with these agents and combinations in relapsed pediatric tumors that may provide applicable future treatment for these patients.